Reasons for low academic achievement among students in middle school - Jaber, Ali dakhel; Ahmed, Aliaa Sobhi (Journal of Educational and Psychological Sciences, 2018)
The current research aimed to identify the causes of low academic achievement among students in middle school and to identify the differences in the level of low academic achievement according to the sex variables (male- female) grade (second- intermediate- middle- third). The basic research sample consisted of (400) students randomly selected from middle schools in the city of Mosul،which reached (8) schools (4) schools on the right side (2) males (2) females and (4) (Males) (2) females and then withdrew a random sample of the class equal to the ranks of these schools and the (25) students from each class. To achieve the objectives of the research،the researchers built a tool for low academic achievement،which consisted of (31) paragraphs with three alternatives (highly applicable،apply moderately،do not apply). The authenticity of the tool was verified by a group of experts and professors in science Educational and psychological supervisors and specialists as the researchers verified their stability in the manner of retesting as the value of the coefficient of stability in this way (0.81). The data were statistically treated using the Pearson correlation coefficient،the single test of a single sample،the test of two independent samples،and the meta- test for correlation coefficient،the appropriate statistical methods were used.The main results of the study were as follows:The most significant results of the study were the difference in the level of low scholastic achievement according to the gender variable and for the males as well as the variable of the grade and for the third- grade average،and there was no significant difference in the level of low academic achievement for the side variable (right – left).
Keywords: low academic achievement; students; middle schools; education